Monitoring RO Plant using Virtual HMI and PLC with Visual Programming Tool - R, Bagawathi; V, Sharmie; J, Anuraga; G, Anusuya Devi; N, Jaanu A S; E, Rajamani M P (2022 3rd International Conference on Electronics and Sustainable Communication Systems (ICESC), 2022)
Human machine interface is a link between the machine and the operator. In other words, HMI - Human machine interface is the point of contact to interact and get the status of the process. HMI is used to display the status of inputs and outputs. The process can be monitored continuously without any intervention. HMI has the ability to receive the data from a programmable logic controller. The communication between the industrial controller and human machine interface can be by RS485 or RS232 communication protocol. In this project, a simulation of reverse osmosis process/plant using Delta HMI and Delta PLC is executed. Reverse osmosis plant contains solenoid valves and pumps. The solenoid valves can be operated by AC voltage or DC voltage. The pumps can be turned on and off using contactors. DOPSoft4.0 and ISPSoft3.15 software's are used to design the components and program.